The Effect of Community Nutrition Education Innovation Based on Social Media Marketing on Knowledge, Attitude, And Behavior To Prevent Stunting - Yuseran, Yuseran; Suryanto, Deni; Basid, Abd; Negara, Candra Kusuma (Sean Institute, 2022)
The Covid-19 pandemic has hampered Stunting prevention and alleviation programs so that facilities are needed to facilitate nutrition education during the pandemic. This study aims to test the innovation of public nutrition education based on social media marketing on Youtube, Facebook, Instagram, TikTok, and Twitter and to measure its effect on cognitive, affective, and behavioral changes. The research design used a quasi-experimental approach with one group pre-test and post-test designs. The research was carried out from September to December 2021. There were 89 respondents spread across five social media. The data were analyzed by using the different paired t-test. Overall for all social media, there was an increase in knowledge of 13.88 points, attitudes of 2.30 points and behavior of 5.81 points. In the three variables, by adding up the delta of change, the social media with the highest increase was TikTok (36.75), followed by Instagram (22.29), Twitter (20.25), Youtube (16.66) and Facebook (12.61). ). Based on the different paired ttest, there are significant differences in knowledge, attitudes, and behavior. The social media that most resulted in changes in target knowledge was TikTok, while changes in target attitudes and behavior were most effective through social media Instagram. The implication of this research is that the findings can be used by stakeholders to promote the prevention and alleviation of Stunting problems more effectively and have a broad impact.